THE INTERNATIONAL PRACTICE OF DRUG SUPPLY IN THE OUTPATIENT SEGMENT - D. V. Lukyantseva; L. S. Mel’nikova; A. P. Tatarinov (Фармакоэкономика, 2018)
The paper examines the international experience of drug supply and the risks faced by countries using various systems of drug provision to the population in the outpatient settings. The option of introducing a system of drug supply or drug insurance with co-payment by outpatients is discussed.